A simple Markov chain for the extended Collatz problem - Aicardi, Michele (IJRDO -Journal of Computer Science Engineering, 2016)
The paper deals with the Collatz problem. A simple extensionof the classic 3n + 1 version is considered allowing the definitionof the algorithm for any target base. Then a simple three ”states”Markov chain is built up to show the probabilistic convergence of thealgorithm to the equilibrium point.